STATE SUPPORT OF SMALL PRIVATE COMPANIES AS THE BASIS FOR SUSTAINABLE RURAL DEVELOPMENT - Aleksei NOSOV; Denis MURZIN; Olga TAGIROVA; Marina FEDOTOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The development of small private companies in agriculture, both in the Russian Federation and in the Penza region, has had a positive trend in recent years. This was facilitated by a variety of state support for small enterprises, and farms. So, during 2014-2018, the grants for developing agriculture were gained by the 199 of small farms, and the amount of financing was 547.3 million rubles. However, there are also constraining factors for the development of small business in the countryside: a decrease in the share of the rural population in the total population of Russia, an imbalance in the ratio of the average monthly income of the rural and urban population, and the lack of modern infrastructure in rural settlements. Directions of systemic changes in the forms and methods of state support of small businesses in the countryside are proposed, which provide an improvement in the quality of life in the countryside through an outstripping growth in the well-being of rural residents and an improvement in social infrastructure.